STUDI TENTANG KUALITAS AUDIT DAN ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Amilin - (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2012)
This study tests the hypothesis that Due Professional Care, audit complexity, time budgetpressure partially affect the audit quality. Respondents in this study are auditors who worked forPublic Accounting Firm in Jakarta choosed by Convenience sampling method. The multipleregression used to test the hypothesis. Using data from a survey amongst 103 auditors in Jakarta,the study suggests that due professional care effect to audit quality, whereas audit complexity andtime budget pressure are not effect to audit quality.